Cost-effectiveness of a primary care-based exercise intervention in perimenopausal women. The FLAMENCO Project - Zuzana Špacírová; David Epstein; Leticia García-Mochón; Virginia A. Aparicio; Milkana Borges-Cosic; M. Puerto López del Amo; José J. Martín-Martín (Elsevier, 2019)
Objective: Adequate physical activity levels and a healthy lifestyle may prevent all kinds of non-communicable diseases, promote well-being and reduce health-care costs among perimenopausal women. This study assessed an exercise programme for perimenopausal women. Method: A total of 150 women (aged 45-64 years) not engaged in regular physical activity were randomly assigned to either a 16 week exercise intervention or to the control group. The study was conducted from the perspective of the National Health System. Health outcomes were quality-adjusted life years (QALYs), measured by the EuroQol-5D-5L questionnaire. The total direct costs of the programme were the costs of visits to primary care, specialty care, emergency, medicines, instructor cost and infrastructure cost. The results were expressed as the incremental cost-effectiveness ratio. Sensitivity analysis was undertaken to test the robustness of the analysis. Results: Mean QALYs over 16 weeks were.228 in the control group and.230 in the intervention group (mean difference: .002; 95% confidence interval [95%CI]: −0.005 to 0.009). Improvements from baseline were greater in the intervention group in all dimensions of the EuroQol-5D-5L but not statistically significant. The total costs at the end of the intervention were 160.38 € in the control group and 167.80 € in the intervention group (mean difference: 7.42 €; 95%CI: −47 to 62). The exercise programme had an incremental cost-effectiveness ratio of 4,686 €/QALY. Conclusions: The programme could be considered cost-effective, although the overall difference in health benefits and costs was very modest. Longer term follow-up is needed. Resumen: Objetivo: El ejercicio físico puede promover el bienestar y reducir los costes de atención médica en las mujeres perimenopáusicas. Este estudio evalúa un programa de ejercicio físico en mujeres perimenopáusicas. Método: Un total de 150 mujeres (de edades comprendidas entre 45 y 64 años) fueron asignadas aleatoriamente al grupo de intervención o al grupo de control. El estudio ha tenido una duración de 16 semanas. Los resultados en salud se han medido en años de vida ajustados por calidad (AVAC) mediante el cuestionario EuroQol-5D-5L. Se ha considerado el total de costes directos del programa, integrado por los costes de las visitas en atención primaria, atención especializada y urgencias, medicamentos, coste del monitor y coste de las instalaciones. Los resultados se han expresado como ratio coste-efectividad incremental. La robustez del modelo se ha contrastado con un análisis de sensibilidad. Resultados: Al final de la intervención, los AVAC fueron 0,228 en el grupo de control y 0,230 en el grupo de intervención (diferencia media: 0,002; intervalo de confianza del 95% [IC95%]: −0,005 a 0,009). La mejoría fue mayor en el grupo de intervención en todas las dimensiones del EuroQol-5D-5L, pero sin significación estadística. Los costes totales al finalizar la intervención han sido de 160,38 € en el grupo de control y 167,80 € en el de intervención (diferencia media: 7,42 €; IC95%: −47 a 62). El programa de ejercicio físico ha tenido una ratio coste-efectividad incremental de 4686 €/AVAC. Conclusión: El programa debe considerarse coste-efectivo, aunque la diferencia en resultados de salud y costes ha sido muy moderada. Se necesita un seguimiento a más largo plazo. Keywords: Cost-benefit analysis, Quality-adjusted life years, Menopause, Exercise, Women, Palabras clave: Análisis de coste-utilidad, Años de vida ajustados por calidad, Menopausia, Ejercicio, Mujeres